Training on the use of google classrooms and google forms for elementary school teachers in Singgahan District, Tuban - Wiratsiwi, Wendri; Mizan, Saeful (Community Empowerment, 2021)
The teachers' ability of SDN Saringembat 1 and SDN Mulyorejo towards technology-based learning media is still low. Therefore, it is still minimally used for online learning. The solution offered is to conduct training on the use of google classroom and google form. The implementation method of this training was by demonstrating, assisting and assigning participants to use the application. Based on the results of the analysis, 95% of participants gained insights and skills related to the use of google classrooms and google forms for online learning. In fact, 65% of them were committed to utilizing these media in learning.